Synthesis, characterization of dinuclear vanadium(III) hydroquinonate- iminodiacetate complexes - Drouza, Chryssoula; Vlasiou, Manolis; Keramidas, Anastasios D. (My University, 2014)
A new VIII complex (1) of 2,5-bis[N,N-bis(carboxymethyl) aminomethyl]hydroquinone (bicah6-) was synthesized by reaction of H6bicah with two equivalents of VCl3 and six equivalents of base in aqueous solution. Crystallographic characterization shows the neutral complex to have a dinuclear hydroquinonate bridged structure. The octahedral environment of vanadium is occupied by the four (N, O, O, O) donor atoms in each binding site of the ligand and two H2O oxygen atoms. Addition of 2,2-bipyridine (bipy) in the reaction mixture resulted in the synthesis of a new dinuclear VIII-μ-bicah6- complex (2) containing a bipy chelated to each vanadium center. The structure of 1 was compared with the respective dinuclear structures of the bicah6- complexes with V IVO2+ (3) and VVO2+ (4). Strong hydrogen bonds between the free, the ligated to vanadium water molecules and the carboxylate and hydroquinonate oxygen atoms result in supramolecular 3D structures by self-assembly of the dinuclear units. These structures are controlled by synthesis conditions and vanadium ion coordination environment. The cyclic voltammogram of 1 showed a reversible VIV+e -⇋VIII process at 0.48 V versus NHE. The EPR spectra of 3 gave a broad peak indicating magnetic interactions between the uncoupled electrons of the two vanadium centers through the hydroquinone bridge. In acidic pHs bellow 2.0, EPR data reveal protonation of the hydroquinonate oxygen and hydrolysis of the complex. The relation of these results with the reduction of VIV and stabilization of VIII ions is discussed.
Keywords: Crystal structure; Electrochemistry; EPR; Hydroquinone; Iminodiacetic acid; Vanadium